Effects of Ethnic Geographical Clustering on Educational Attainment in the Netherlands - Thomas de Graaff; Cees Gorter; Peter Nijkamp (Tinbergen Institute, 2001)
Contemporary migration studies witness an increasing interest in the socio-economicrole of networks of migrants. Such networks are sometimes even regarded as the mostimportant attraction and location factors for migration, and may even exceed purelyeconomic factors like unemployment and wage levels in importance. The empiricalmeasurement and analysis of migrants' networks however, is far from easy. Usually, thesize of immigrant networks in a city is proxied by means of the share of foreigners, whilemuch less attention is given to the spatial distribution of immigrants. This paper aims toaddress the empirical assessment of spatial clustering of socio-cultural groups in thecity. It does so by modifying a geographical concentration measure developed by Ellisonand Glaeser (the gamma coefficient), with a view to the measurement of spatial clusteringof migrants in the Netherlands. Because of the scale-independent character of thegamma coefficient, we are able to investigate the degree of ethnic clustering at twodifferent spatial levels, namely urban districts and urban neighborhoods.The second research aim of the present paper centers around the explanation ofthe educational attainment of ethnic children with the help of this clustering index incombination with parental attributes and social network characteristics. The resultsobtained indicate that educational attainment may depend on geographical clustering,but that the geographical scale of analysis is highly influential on the findings.
Keywords: I2; R2; 330; Ethnic minorities; geographical concentration Educational Attainment; Ethnische Gruppe; Räumliche Verteilung; Clusteranalyse; Bildung; Niederlande